Detection of Saffold viruses from children with acute respiratory infections in Yamagata, Japan, between 2008 and 2015. Issue 1 (12th September 2017) - Itagaki, Tsutomu; Aoki, Yoko; Matoba, Yohei; Tanaka, Shizuka; Ikeda, Tatsuya; Matsuzaki, Yoko; Mizuta, Katsumi
Abstract : Although Saffold virus (SAFV) was reported as a novel human cardiovirus in 2007, no causative association between SAFV and clinical disease has been proven and the longitudinal epidemiology of SAFVs is not available. To establish the relationship between SAFVs and acute respiratory infections (ARIs) and to clarify the longitudinal epidemiology of SAFVs, 7258 nasopharyngeal specimens were collected from children with ARIs in Yamagata, Japan between 2008 and 2015. The specimens were inoculated on a microplate including six cell lines as part of routine surveillance, and molecular screening was performed for SAFVs using a reverse transcription (RT)‐PCR method. Throughout the study period, 95 (1.3%) SAFV genotype 2 (SAFV2), and 28 (0.4%) SAFV3 were detected, mainly between September and November. There were two outbreaks of SAFV2 in 2009 and 2013, and one outbreak of SAFV3 in 2012 and the positive rates during these outbreaks were 12.1% (53/439), 11% (35/319), and 4.4% (20/453), respectively. Sixty‐three SAFV2 and 28 SAFV3 strains were detected as a single virus from children with ARIs such as pharyngitis, herpangina, and tonsillitis. These results suggested that SAFV2 and SAFV3 are possible causative agents of ARIs among children and their infections occur mainly in the autumn season in Japan.